2013
DOI: 10.1007/s00011-013-0602-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary component p-coumaric acid suppresses monosodium urate crystal-induced inflammation in rats

Abstract: The results of this study reveal the potential anti-inflammatory effect of p-Coumaric acid against monosodium urate crystal-induced inflammation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
3
30
0
1
Order By: Relevance
“…p-CA also decreased the ROS levels, but no statistical difference was found. In conjunction with previous reports and our results that QC and p-CA inhibited Aβ-induced microglial activity, suppressed ROS production, and inhibited NF-κB activity in BV-2 microglial cells48,49,50 , we may conclude that the structures of kaempferol and p-CA played a vital role in inhibiting neuroinflammation.…”
supporting
confidence: 81%
“…p-CA also decreased the ROS levels, but no statistical difference was found. In conjunction with previous reports and our results that QC and p-CA inhibited Aβ-induced microglial activity, suppressed ROS production, and inhibited NF-κB activity in BV-2 microglial cells48,49,50 , we may conclude that the structures of kaempferol and p-CA played a vital role in inhibiting neuroinflammation.…”
supporting
confidence: 81%
“…59 It has been shown that p-CA suppresses the infl ammation caused by monosodium urate crystals in rats. 60 P-CA has been shown the immunomodulatory and anti-infl ammatory effect on experimental infl ammation in rats. 61 In this study, oxidant-antioxidant and infl ammation parameters in the R-IR injury model using p-CA were examined by biochemical method.…”
Section: Discussionmentioning
confidence: 97%
“…Flavonoids are leading miscellaneous assembly of phytonutrients to present virtually almost in all fruits and vegetable with more than 6000 types [13]. The flavonoids basic structure of comprises of a frame of diphenyl propane, having two aromatic benzene (ring A and B) allied through a three carbon chain which forms a closed pyran ring using benzene A ring [15].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Glycoside forms consist of two types of di-glycosides, L-rhamnosylglucosyl derivatives, which are classified as neohesperidosides and rutinosides, connected through 1,2 or 1,6 inter glycosidic bond, respectively. It had excellent potential to control Citrus: An Ancient Fruits of Promise for Health Benefits http://dx.doi.org/10.5772/intechopen.79686 many chronic diseases and suppressed the infectious in the body [13,14]. The classification of flavonoids showed in Figure 2.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation